SOSIALISASI PKM KESEHATAN PERAN PENTING LINTAS SEKTOR DALAM PERCEPATAN PENURUNAN STUNTING WUJUDKAN GENERASI EMAS DESA BULAKAN KOTA CILEGON - Juhandi, Juhandi; Hanafiah, Hafidz; Ilyas, Muhammad; Hayan, Maulana Thoriqul; Yuliano, Muhammad Ilhan (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Stunting is fancy language for malnutrition, before independence Indonesia experienced extraordinary cases of malnutrition. The aim of implementing Community Service (PKM) was initiated by dozens of cases of stunting in the Real Work Lecture (KKM) environment of Group 42 of Bina Bangsa University, namely Bulakan Village, Cilegon City, Banten Province. The first step taken before carrying out the socialization of PKM Health was to conduct a survey and then coordinate with the local village head and Bulakan Village Health Center officers. After participating in cross-sector stunting socialization, 20 participants participated. The expected result is that stunting participants, sub-district/village officials, and health workers can support the acceleration of stunting reduction by doing various things that have been explained during the socialization